Hypothalamic-pituitary-adrenal axis, childhood adversity and adolescent nonsuicidal self-injury. (December 2016) - Reichl, Corinna; Heyer, Anne; Brunner, Romuald; Parzer, Peter; Völker, Julia Madeleine; Resch, Franz; Kaess, Michael
Highlights: Non-suicidal self-injury (NSSI) was associated with altered HPA axis functioning. Adolescents engaging in NSSI showed increased cortisol awakening responses. Hair cortisol and the diurnal slope were not altered in adolescents with NSSI. Adolescents with NSSI showed a steeper diurnal slope following childhood adversity. Abstract: Background: Whereas childhood adversity (CA) and the hypothalamus-pituitary-adrenal (HPA) axis have been suggested to play a major role in the etiology of non-suicidal self-injury (NSSI), no study has thus far investigated both its associations and interactions with adolescent NSSI. Method: We investigated CA (antipathy, neglect, physical, psychological, and sexual abuse) and indices of HPA axis activity (salivary and hair cortisol) in a clinical sample of 26 adolescents engaging in NSSI and 26 age- and gender-matched healthy controls (HC). We used standardized interviews for the assessment of CA (CECA), NSSI (SITBI-G), and axis I diagnoses (MINI-KID). Salivary cortisol sampling was surveyed using a monitoring system and instructed via telephone calls. Results: Adolescents engaging in NSSI exhibited significantly higher cortisol awakening responses compared to HC. No differences were found with respect to the diurnal slope or hair cortisol. In the presence of CA, healthy adolescents showed flatted diurnal cortisol slopes while those engaging in NSSI exhibited significantly steeper ones. Conclusions: Our findings indicate that adolescents engaging in NSSI may exhibit a stronger cortisol awakening response, potentially in expectation of strain. However, elevated cortisol levels may not be maintained throughout the day, especially among adolescents with a history of CA.